2021
DOI: 10.3390/ijms222112063
|View full text |Cite
|
Sign up to set email alerts
|

Clioquinol Decreases Levels of Phosphorylated, Truncated, and Oligomerized Tau Protein

Abstract: The neuropathological hallmarks of Alzheimer’s disease (AD) are senile plaques (SPs), which are composed of amyloid β protein (Aβ), and neurofibrillary tangles (NFTs), which consist of highly phosphorylated tau protein. As bio-metal imbalance may be involved in the formation of NFT and SPs, metal regulation may be a direction for AD treatment. Clioquinol (CQ) is a metal-protein attenuating compound with mild chelating effects for Zn2+ and Cu2+, and CQ can not only detach metals from SPs, but also decrease amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Skin infections can be treated with topical medicines containing clioquinol (148). Furthermore, clioquinol was once widely used as an anti-infective, particularly for diarrhea (149). LY294002 is a highly selective inhibitor of phosphatidylinositol 3 kinase (150,151).…”
Section: Discussionmentioning
confidence: 99%
“…Skin infections can be treated with topical medicines containing clioquinol (148). Furthermore, clioquinol was once widely used as an anti-infective, particularly for diarrhea (149). LY294002 is a highly selective inhibitor of phosphatidylinositol 3 kinase (150,151).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that clioquinol downregulates β- and γ-secretase and APP expression in the brain ( Wang et al, 2012 ). In vitro experiment demonstrated that clioquinol was able to degrade oligomerized tau and reduce tau tangles ( Lin et al, 2021 ). The effect of clioquinol in AD was also validated in a randomized controlled trial involving patients with moderate-to-severe AD, as oral clioquinol compared to placebo led to slower cognitive decline and reduced CSF Aβ42 ( Ritchie et al, 2003 ).…”
Section: Targeting Iron Dyshomeostasis and Ferroptosis To Treat Alzhe...mentioning
confidence: 99%
“…The activity of GSK-3β was negatively correlated with the phosphorylation degree of enemy Ser9, which means the higher the dephosphorylation degree of Ser9, the higher the level of GSK-3β and the phosphorylation degree of related tau protein will increase [19] . Tau protein phosphorylation is also regulated by PP2A-based protein phosphatase, which inhibits tau protein phosphorylation more strongly than other protein kinases [20,21] . The results indicated that the phosphorylation degree of tau protein at the sites Thr231, S396 and S404 in the observation group was higher than that in the control group, which may be associated with the increase of GSK-3β protein expression and the decrease of PP2A protein expression [22][23][24] .…”
Section: Resultsmentioning
confidence: 99%